Analysis of the use of a 4 kW BLDC motor to drive a 1GT electric passenger boat - Anggara Fuad Al Amin; Supari Supari; Satria Pinandita (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
Passenger boats are a means of transportation that is used to transport passengers to a destination. One of them is a boat for passengers to visit the religious tour of Sheikh Mudzakir's grave. The religious tourism location of Sheikh Mudzakir's grave is located about 2 km north of Blekok Island. However, this passenger boat still relies on fuel oil as fuel to drive the passenger boat's combustion engine. Research on electric boats was carried out by several students at Semarang University. This electric boat uses solar panel technology installed on it to harvest solar energy and convert it into electricity which is stored in batteries to move the boat. This electric boat uses a 3 Phase 1 HP 4 Pole electric motor that uses solar charge control and an inverter as a converter from 12 V DC to 380 V AC. Using a 3 Phase Electric Motor requires a large amount of electricity, because it requires electricity that must be converted to voltage. high, will result in high loss, so that the efficiency of battery use is relatively wasteful. The aim of this research is to carry out tests using a 4 kW 72 Volt BLDC Motor as an alternative solution to replace previous research which used a 3 Phase 1 HP Motor on an electric passenger boat. The results show that the motor rotation of a 4 kW 72 Volt BLDC motor tends to be greater than using a 3 Phase 1 HP electric motor and a 9 HP fuel engine, where previous research showed that the speed of an electric boat can only reach a maximum speed of 4.4 Knots at high mode gas level. , while using a 4 kW 72 Volt BLDC motor it can reach a speed of 8 Knots, which is a huge improvement. Very suitable for using a 4 kW 72 Volt BLDC motor on a 1GT electric boat